To what extent do social enterprises contribute to fostering social innovation and driving positive social change In Portugal? - case study analysis & survey analysis - Braasch, Liese (2024)
The research investigates the degree to which social enterprises facilitate social innovation and propel constructive social transformation in Portugal. Social enterprises operate in an environment where social and economic goals are pursued concurrently, combining market driven tactics with social aims. However, challenges related to legal recognition, financial sustainability, and ecosystem support persist. The thesis underscores the need for robust frameworks to enhance the effectiveness of social enterprises and suggests further integration of these entities into the social sector. In addition to making recommendations for future research, practitioners, and policymakers, this research advances the theoretical and practical understanding of social enterprises.